The differing characteristics of Brachypodium pinnatum (L.) P. Beauv. and B. sylvaticum (Huds.) P. Beauv. - Paszko, Beata (Biodiversity: Research and Conservation, 2007)
Brachypodium pinnatum and B. sylvaticum are two well known, closely related and similar species within the genus Brachypodium. A number of differing characteristics between these two species is examined. B. pinnatum and B. sylvaticum cannot be distinguished on the basis of qualitative characteristics suggested by different taxonomists, such as the shape of the ligule, hairiness of leaves and sheaths, and presence or absence of hairs on the leaf margins.